Current approaches to reduce or eliminate mitochondrial DNA mutations - Yang, Liang; Mei, Tingfang; Lin, Xiaobing; Tang, Haite; Wu, Yi; Wang, Rui; Liu, Jinglei; Shah, Zahir; Liu, Xingguo (Science China. Life sciences, 2016)
Mitochondrial DNA （mtDNA） mutations have been impli- cated in a broad range of disorders which severely affect human health （Wallace, 1999）. Some drugs have been developed to slow down pathological changes of mitochon- drial disorders. However, there is no effective treatment for patients with mtDNA mutations, mtDNA is less protected and has fewer repair mechanisms than nuclear DNA （nDNA）. Such a reality results in a much higher mutation rate in mtDNA than that in nDNA. The mixture of mutated mtDNA versus wild-type mtDNA is known as hetero- plasmy. Mitochondrial threshold effect refers to the fact that mtDNA mutation must accumulate to high proportions （60%-90%） before respiratory activity is affected （Schon et al., 2012）. It is feasible to selectively reduce the levels of mu- tated mtDNA while sparing wild-type mtDNA to skew this ratio back to a healthier range. Here, we describe the link between mtDNA mutation and mitochondrial diseases, and we summarize several newly developed approaches with regard to the reduction or elimination of mtDNA mutation in mammals. These methods include nuclear gene modula- tion, molecular approaches targeting mutated mtDNA, mtDNA replacement, and induced pluripotent stem cell （iPSC） modeling. These various methods have their own advantages and limitations.